The (in)stability of money demand in the Euro Area: Lessons from a cross-country analysis - Dieter Nautz; Ulrike Rondorf (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
The instability of standard money demand functions has undermined the role of monetary aggregates for monetary policy analysis in the euro area. This paper uses country-specific monetary aggregates to shed more light on the economics behind the instability of euro area money demand. Our results obtained from panel estimation indicate that the observed instability of standard money demand functions could be explained by omitted variables like e.g. technological progress that are important for money demand but constant across member countries.
Keywords: E41; E51; E52; 330; Money demand; cross-country analysis; panel error correction model; euro area; Geldnachfrage; Panel; Fehlerkorrekturmodell; Schätzung; Eurozone